STRENGTHENING RELIGIOUS MODERATION THROUGH THE ICEBERG ANALYSIS MODEL AS AN EFFORT TO COUNTERACT COGNITIVE BIAS AMONG RADICAL GROUPS FOR ISLAMIC EDUCATION STUDENTS UIN FATMAWATI SUKARNO BENGKULU - Pasmah Chandra; Adam Nasution (Adisam Publisher, 2026)
The aim of this research is to find out the process of strengthening religious moderation through developing the iceberg analysis model as an effort to counteract the cognitive bias of radicals in Islamic religious education students at UIN Famawati Sukarno Bengkulu and to find out the effectiveness of developing the iceberg analysis model as an effort to counteract the cognitive bias of radicals in students Islamic religious education at UIN Famawati Sukarno Bengkulu. The research method that will be used is Participatory Action Research (PAR). Through this method, researchers will involve themselves directly in strengthening religious moderation through the Iceberg analysis model as an effort to counteract the cognitive bias of radicals in Islamic Religious Education students at UIN Fatmawati Sukarno Bengkulu. The results of the research are that Islamic Religious Education Students identified events related to moderate/immoderate actions. Islamic Religious Education Students identify events related to the cognitive bias of radicals, Islamic Religious Education Students formulate patterns and trends, cause structures and determine mental models. Islamic Religious Education Students formulate theoretical actions. Carrying out change action movements through; rethinking, redesigning, reframing to actually reacting.